KLASIFIKASI PETROFISIKA TIPE BATUAN UNTUK MEMPREDIKSI KUALITAS RESERVOAR PASIR SERPIHAN PADA FORMASI TALANG AKAR, CEKUNGAN ONWJ - Feni Priyanka; Bagus Sapto Mulyatno; Riezal Ariffiandhany (Jurnal Geofisika Eksplorasi, 2018)
Hydrocarbons were accumulated in reservoir, the reservoir has a lot of types depending on the geological conditions and the constituent mineral. In ONWJ basins, sub-basins Arjuna, Talang Akar Formation is sand splintersreservoir type. The presence of clay in a reservoir will reduce the resistivity and increase thesaturation, so it takes a multimineral analysis and the reservoir qualityclassification. In this study, physical properties (porosity, permeability, Rw, and saturation) and the quality of the reservoir can be identified through petrophysical analysis by utilizing log data and core analysis, and the rocktypeprediction(using R35 Winland or HFU method). In this study 5 wells (IX-A1, IX-13, IX-4, IX-7 and IX-8)used and found eight hydrocarbon zones, 6 are validated by the DST (drill steam test)data, androck type method that suitable is the method of HFU (hydraulic flow units) due to the coefficient of correlation between porosity and permeability shows a value of 0.75, based on the calculations, the eight types of rock is conclude, where the dominance of the rock typeis the type 12 with a pore size between 5-10 microns, type reservoir rocks in this study belong to the lithofacies distributary channel and mouthbar sand. By knowing the petrophysical property values, it can determine reservoir productivity and determine the zone eligible to be produced or not, by using curve SMLP (Stratigraphic Modified Lorenz Plot).